Y=4x-1 because it can be the only one
The simplified form of the expression [5.5(x+6 1/2)-(x+9 1/3)-(19-x)] is 11x/2 + 89/12
<h3>What is the simplified form of the expression</h3>
Given the expression;
5.5(x+6 1/2) - (x+9 1/3) - (19-x)
First, we convert 6 1/2, 9 1/3 and 5.5 to an improper fraction
6 1/2 = 13/2, 9 1/3 = 28/3 and 5.5 = 11/2
So, we have
(11/2)( x + 13/2 ) - ( x + 28/3 ) - ( 19 - x )
Next, we remove the parentheses
11x/2 + 143/4 - x - 28/3 - 19 + x
11x/2 + 143/4 - 28/3 - 19
11x/2 + 317/12 - 19
11x/2 + 89/12
Therefore, the simplified form of the expression [5.5(x+6 1/2)-(x+9 1/3)-(19-x)] is 11x/2 + 89/12.
Learn more about fractions here: brainly.com/question/28039882
#SPJ1
Answer:
SAS (side angle side)
Step-by-step explanation:
We have a pair of corresponding sides and the included angle. The angle is equal, but the sides are a fraction of the other triangle's side and has an equal rate.
2AC=DF
2AB=DE
The triangles are congruent
On your calculator, use the normalcdf() function, enter the Lower Limit, Upper Limit, Mean, and Standard deviation.
The mean and standard deviation are given to you. You want to find "less than 13.5 seconds", meaning that 13.5 is the maximum "Upper Limit" and 0 would be the Lower Limit because we can pretend 0 second is the minimum. Don't worry about negatives, in this scenario, values like "-5 seconds" are impossible.
Enter normalcdf(0, 13.5, 13.56, 2.24) in a calculator and the output result is the answer.
Step-by-step explanation:
The point (12, 5)
x = 12, y = 5
=> r =√12²+5² =√144+25= √169=13
so, cos θ = x/r = 12/13 and
cot θ = x/y = 12/5